A metonímia do desejo : um estudo etnográfico da clínica lacaniana em Londrina-Pr - Antonio, Maria Carolina de Araujo (Universidade Federal de São Carlos, 2010)
This research, realized in Londrina (PR) through in-depth qualitative interviews with psychoanalysts and people who do lacanian analysis, and participant observation in a group of lacanian studies, aims to analyse, in this specific ethnographic context, a version of the modern Western notion of person produced by the lacanian clinic based on the concepts such as metonymic desire, structural lack and desiring subject. The forms of subjectivity handled by this method of treatment encompass concepts of suffering, unconscious, healing, health and disease which operate as a system of thought assimilated into the production of a new conception of the self. This conception appeared articulated in the process of constitution of a desiring subject, resulting from a theory of desire that characterizes the lack as a way of being. Thus, the Lacanian psychoanalysis capitalizing certain notion of person that serves as a translation of a code present in the Western capitalist society, as the free and autonomous individual condemned to an endless quest for satisfaction that can never be achieved. The fieldwork also allowed to reach, besides the specifics of Lacanianism in Londrina, part of the universe "psi" of that city.
Keywords: Antropologia social; Psicanálise lacaniana; Psicoterapia; Noção de pessoa; Processo terapêutico; CIENCIAS HUMANAS::ANTROPOLOGIA